Development of the co-operative movement in northern Canada since 1963 - Sprudzs, Aleksandrs (Polar Record, 1967)
The Second Conference of the Arctic Co-operatives was held at Poyungnituk, 19-28 April 1966. The first conference, held three years earlier at Frobisher Bay, had asked the Department of Indian Affairs and Northern Development, which is sponsoring the co-operative development programme in the Canadian north, for assistance in establishing a strong central co-operative marketing agency to develop new markets for the increasing volume of crafts, and to exercise quality control. The Department agreed to discuss this proposal with the Co-operative Union of Canada and the Conseil Canadien de la Cooperation and to prepare a paper outlining its findings in detail. The delegates were to recommend to their co-operatives that they should consider the idea of a central marketing agency.